2011
DOI: 10.1038/ja.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

Efflux pump genes and antimicrobial resistance of Pseudomonas aeruginosa strains isolated from lower respiratory tract infections acquired in an intensive care unit

Abstract: The aim of this study was to determine the antimicrobial resistance rates and the resistance genes associated with efflux pumps of Pseudomonas aeruginosa strains isolated from the patients who acquired lower respiratory tract infection (LRTI) in intensive care unit (ICU). Fifty P. aeruginosa strains isolated from the lower respiratory tract specimens of the patients who acquired LRTIs in ICU were included in this study. P. aeruginosa strains were isolated from tracheal aspirate (27), bronchoalveolar lavage (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
(29 reference statements)
3
15
1
Order By: Relevance
“…Figure (4) shows agarose gel electrophoresis for two efflux system genes(mexX and mexY). In the study of Cabot et al (28) they showed that the prevalence rate of mexY gene without over expression was 81.5% and this result is not in line of the current study, while Ozer et al (29) illustrated that the prevalence rate of mexX was 4% and this result not agreed with the current study. The genes coding for the modifying enzymes either present alone or in combination between two genes or three genes but can be seen none of the isolates in the current study was observed to contain the 4 detected genes.…”
Section: Resultscontrasting
confidence: 80%
“…Figure (4) shows agarose gel electrophoresis for two efflux system genes(mexX and mexY). In the study of Cabot et al (28) they showed that the prevalence rate of mexY gene without over expression was 81.5% and this result is not in line of the current study, while Ozer et al (29) illustrated that the prevalence rate of mexX was 4% and this result not agreed with the current study. The genes coding for the modifying enzymes either present alone or in combination between two genes or three genes but can be seen none of the isolates in the current study was observed to contain the 4 detected genes.…”
Section: Resultscontrasting
confidence: 80%
“…Similar results were reported by Arabestani et al, (2015), who observed a signi cant positive correlation between pump activity and antimicrobial resistance [45]. Ozer et al, (2012) reported a consistent positive correlation between MexAB-OprM expression and multidrug resistance in 50 P. aeruginosa clinical strains [46]. However, in our study, of the P. aeruginosa strains that showed MexAB-OprM activity (phenotypic positive-strains), only in 52.9% the MexAB-OprM e ux pump was the most likely cause of resistance (+), in the remaining 47% of the strains the MexAB-OprM e ux pump was contributing to the resistance (*), which demonstrated that although the MexAB-OprM pump shows positive activity and contributes to resistance, this is not the only mechanism of resistance in these strains [13].…”
Section: Discussionsupporting
confidence: 83%
“…[5] RND pumps consist of three subunit including membrane fusion protein (MFP), an outer membrane factor (OMF), and a cytoplasmic membrane transporter. [56] MexAB-OprM and MexCD-OprJ, which are members of RND efflux pumps family, have the wide substrate of antibiotics such as, β-lactam class (aztreonam, ceftazidime) and fluoroquinolones. [7] Active efflux pumps decrease intracellular concentration of drug by pumping it to out.…”
Section: Introductionmentioning
confidence: 99%